Combined and individual doxorubicin/vancomycin drug loading, release kinetics and apatite formation for the CaO–CuO–P2O5–SiO2–B2O3 mesoporous glasses. Issue 56 (25th May 2016) - Kaur, Gurbinder; Pandey, O. P.; Singh, K.; Chudasama, Bhupendra; Kumar, V.
Abstract : The novel mesoporous glass series based on (25 − x )CaO– x CuO–10P2 O5 –5B2 O3 –60SiO2 ( x = 2.5, 5, 7.5, 10) has been prepared using the sol–gel technique. Abstract : The novel mesoporous glass series based on (25 − x )CaO– x CuO–10P2 O5 –5B2 O3 –60SiO2 ( x = 2.5, 5, 7.5, 10) has been prepared using the sol–gel technique. The pore size of the prepared mesoporous bioactive glasses (MBG) lies between 6.1 and 9.1 nm, whereas the surface area varies from 281 to 418 m 2 g −1 . The pH variation, zeta potential, Fourier transform infra-red (FTIR) spectroscopy and simulated body fluid (SBF) studies indicated the in vitro bioactivity of all the MBGs. The MBGs were loaded with the anticancerous and antibacterial drugs, doxorubicin and vancomycin, respectively. The increasing copper content predominantly influenced the bioactive properties as well as the drug loading and release kinetics of the doxorubicin and vancomycin drugs. In addition to the individual loading of drugs in the MBG, both the drugs were also loaded together in the MBG to investigate the effect of combined loading on the release capability of the MBGs.